Association among financial development, economic growth, ecological footprint, and carbon emissions in India: a VECM analysis - Sarika Keswani; Narmada Mariayala; Mohit Kumar; Vippa Dhingra (Cogent Social Sciences)
This study explores the complex relationships between Financial Development, Economic Growth, Ecological Footprint, and Carbon Emissions, highlighting the environmental impacts of India’s economic and financial growth. As the third-largest carbon emitter globally, India’s sustainable development challenges make this research crucial for policymakers. Covering the period from 1990 to 2022, the study employs a Vector Error Correction Model (VECM) to identify both short- and long-term cointegration relationships among these variables. The VECM-based Granger causality test reveals significant long-term connections between carbon emissions, financial development, economic growth, and the ecological footprint. Interestingly, the results indicate a positive correlation, suggesting that carbon emissions increases as economic growth, financial development, and ecological footprint increase. These findings provide valuable insights for designing policies that balance economic advancement with environmental protection in India.